Proceedings of the International Conference on Signal, Networks, Computing, and Systems ICSNCS 2016, Volume 1 - Lobiyal, Daya K.; Mohapatra, Durga Prasad; Nagar, Atulya; Sahoo, Manmath N.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2017)
The book is a collection of high-quality peer-reviewed research papers presented in the first International Conference on Signal, Networks, Computing, and Systems (ICSNCS 2016) held at Jawaharlal Nehru University, New Delhi, India during February 25-27, 2016. The book is organized in to two volumes and primarily focuses on theory and applications in the broad areas of communication technology, computer science and information security. The book aims to bring together the latest scientific research works of academic scientists, professors, research scholars and students in the areas of signal, networks, computing and systems detailing the practical challenges encountered and the solutions adopted.
Part 1. Signal Processing Systems and Applications: Chapter 1. DFT-DCT Combination Based Novel Feature Extraction Method for Enhanced Iris Recognition -- Chapter 2. Novel Digital Image Watermarking in SWT+SVD Domain -- Chapter 3. An Improved Histogram Bin Shifting Based Reversible Data Hiding of Color Images -- Chapter 4. Face Recognition Using Background Removal Based on Eccentricity and Area Using YCbCr and HSV Color Models -- Chapter 5. An Efficient Multi-focus Image Fusion Approach Based on DWT -- Chapter 6. A Novel Fuzzy Filter for Mixed Impulse Gaussian Noise from Color Images -- Chapter 7. Face Recognition Using Snakes Algorithm and Skin Detection Based Face Localization -- Chapter 8. Quantifiable Image Nearness Approach Using Descriptive Neighbourhood -- Chapter 9. Robust Speaker Verification Using GFCC Based i-vectors -- Chapter 10. Enhanced Automatic Speech Recognition with Non-acoustic Parameters.-Chapter 11. Dynamic Gesture Recognition - A Machine Vision Based Approach -- Chapter 12.Medical Image Security with Cheater Identification Using Secret Sharing Scheme -- Chapter 13. The Role of Fractal Dimension, Lacunarity and Multifractal Dimension for Texture Analysis in SAR Image- A Comparison Based Analysis -- Chapter 14. Efficient Storage and Processing of Video Data for Moving Object Detection Using Hadoop/MapReduce -- Chapter 15. Performance Evaluation of Digital Color Image Watermarking Using Column Walsh Wavelet Transform -- Chapter 16.Structural (Shape) Feature Extraction for Ear Biometric System -- Part 2. Networking Theory and Distributed Systems: Chapter 17. DHAC Based Routing in Wireless Sensor Network with Asymmetric Links -- Chapter 18. Automatization of AAOCC to find Trust Score of Websites -- Chapter 19. A Multi-level Weight Based Routing Algorithm for Prolonging Network Lifetime in Cluster Based Sensor Networks -- Chapter 20. An Approach to Optimize Unnecessary Energy Consumption During Dynamic Routing in Wireless Sensor Networks -- Chapter 21. Game Theoretic Modeling of Gray Hole Attacks in Wireless Ad Hoc Networks -- Chapter 22. Chi-Square Based Mobile Radio Propagation Model Analysis and Validation -- Chapter 23. Collision Theory Based Sentiment Detection of Twitter Using Discourse Relations -- Chapter 24. Malicious Account Detection Based on Short URLs in Twitter -- Chapter 25. Distance, Energy and Link Quality Based Routing Protocol for Internet of Things -- Chapter 26. Effect and Suppression of Noise in 2D PC/OOC Scheme for Optical CDMA Systems -- Chapter 27. On-the-Fly Segment Density (OFSD) in Adaptive Beaconing System (ABS) Based Connectivity-Aware Geocast Routing (CAGR) in VANETs -- Chapter 28.Investigation and Analysis of Energy Efficiency in Distributed Antenna System: Technology towards Green Communications -- Chapter 29. A Novel Trust Based Access Control Model for Cloud Environment -- Chapter 30. Live News Streams Extraction for Visualization of Stock Market Trends -- Chapter 31. Categorization of Cloud Workload Types with Clustering -- Chapter 32.Development of a General Search Based Path Follower in Real Time Environment -- Chapter 33. SDN Architecture on Fog Devices for Realtime Traffic Management: A Case Study -- Chapter 34.Maximizing Network Lifetime of Wireless Sensor Networks: An Energy Harvesting Approach.-Chapter 35. Hybrid Network Intrusion Detection Systems: A Decade's Perspective. .
Keywords: Telecommunication; Signal processing; Computer networks .; Communications Engineering, Networks; Signal, Speech and Image Processing; Computer Communication Networks